Understanding the Dutch Eating Behavior Questionnaire: Insights from Medical Students - Akhlaq, Sana; Yousuf, Umara (Journal of Postgraduate Medical Institute, 2025)
Background: Eating behaviors significantly influence health, particularly among medical students, who face academic stress and lifestyle challenges. This study explores the association between eating behaviors (restrained, emotional, and external eating) and demographic factors among medical students at Gujranwala Medical College, Pakistan. Methods: A cross-sectional observational study was conducted from September to November 2024 using the Dutch Eating Behavior Questionnaire (DEBQ). A sample of 228 students was analyzed via SPSS version 26 for descriptive and inferential statistics. Cronbach’s alpha was 0.79, indicating good internal consistency. Regression analysis examined relationships between eating behaviors and predictors, including academic year, gender, and residency status. Results: The sample comprised 64% females and 70% hostel residents. Restrained eating behavior showed a significant association with academic year (p = 0.014), indicating that senior students were more likely to practice restrained eating. Emotional and external eating behaviors were not significantly associated with demographic predictors. Factor analysis revealed distinct patterns of eating behaviors among subgroups, with females and hostel residents exhibiting higher emotional and external eating tendencies. Conclusion: Academic year emerged as a significant predictor of restrained eating, while emotional and external eating behaviors were more influenced by gender and residency status. These findings underscore the need for targeted interventions addressing stress and promoting healthier eating practices among medical students. Future research should include larger, diverse populations to understand the multifactorial influences on eating behaviors better.